Populism and the (Italian) crisis: The voters and the context. (August 2021) - Caiani, Manuela; Padoan, Enrico
This article, focusing on Italy, aims to broaden our understanding of the recent striking electoral fortunes of (differing types of) populism in the country, by locating them within multiple crises (political, economic, migration) that have shocked Europe in the last two decades. By combining individual-level survey data on voters with organizational-level interviews conducted with national and local representatives and activists of the Five Star Movement and the League, the role played by these crises in the two different Italian populisms will be disentangled from 'demand' and 'supply' perspectives – which are usually treated in isolation. The findings indicate a coherence between the political parties' message and their respective potential voters' orientations and attitudes (with regard to the three crises), underlining the ability of different varieties of populism to intercept (and mobilize) different grievances: whereas the economic crisis of representation is a key ingredient of both the populists' success, the cultural crisis is more salient for the exclusionary populist League, while the political crisis is more salient for the inclusionary 5SM. For both the mobilization and representation of those citizens unsatisfied with traditional politics seems crucial. These different causes of success appear to be a useful lens through which to examine the failure of an attempt to govern by combining two differing types of populism.